Under the medical gaze : facts and fictions of chronic pain - Greenhalgh, Susan (University of California Press, 2001)
This compelling account of the author's experience with a chronic pain disorder and subsequent interaction with the American health care system goes to the heart of the workings of power and culture in the biomedical domain. It is a medical whodunit full of mysterious misdiagnosis, subtle power plays, and shrewd detective work.